Utility of Merchant View Radiographs for Assessment of TT-TG: A Comparison to MRI. Issue 7 (30th July 2018) - Bernholt, David; Lamplot, Joseph D.; Eutsler, Eric; Nepple, Jeffrey J.
Objectives: Lateralization of the tibial tubercle plays a significant role in the pathophysiology of patellar instability and is most often assessed by the tibial tubercle to trochlear groove distance (TT-TG) measured on CT or MRI with the knee in extension. However, tracking of the patella in 30 to 45 degrees of flexion has been suggested to be of greater clinical significance. Merchant radiographs can demonstrate the position of the tibial tubercle relative to the trochlear groove in this range of flexion and thus may serve as a valuable tool in the assessment of patellar tracking. The purpose of the current study was (1) to validate radiographic assessment of the merchant view TT-TG and (2) to determine the correlation with MRI-based measurements. Methods: To validate Merchant TT-TG as a marker of the position of the tibial tubercle, 41 patients between the ages of 10-18 had standardized Merchant radiographs in 45 degrees flexion yielding imaging of 82 knees. Lead markers were placed upon the skin centered over the tibial tubercle based on palpation. Radiographs were collected and analyzed. The TT-TG was measured as the distance between lines centered over the deepest point of the trochlear groove and the center of the tibial tubercle and perpendicular to the anterior condylar axis. In order to correlate Merchant TT-TG to MRI TT-TG, 16 additional patients were added to reach a total of 30 patients with a Merchant radiograph and MRI, as power calculation determined 29 knees needed to detect a Pearson correlation coefficient (PCC) of .500. There was excellent interobserver reliability between two readers for Merchant TT-TG with and without use of a radiographic marker (ICC = .975 and .923 respectively). Results: The tibial tubercle could be identified on Merchant radiograph in 67 images (81.7%). Merchant TT-TG measured with use of a marker was very strongly correlated measurement based on bony landmarks alone (PCC = .848). The Merchant TT-TG measured with bony landmarks alone was strongly correlated to MRI TT-TG (PCC = .602). The strength of this correlation was increased by standardizing TT-TG by patellar width (PCC = .710). MRI TT-TG was increased in patients with patellar instability at 13.9 mm compared to 10.5 mm (p <.01); Merchant TT-TG was also increased in patients with patellar instability at 9.1 mm compared to 1.9 mm (p < .001). Conclusion: Standardized Merchant radiographs without radiographic markers allow for assessment of TT-TG in the majority of patients. Merchant TT-TG strongly correlates with MRI TT-TG but measured 5-8 mm smaller than MRI TT-TG.